Higher, faster, stronger for triple SATB chorus with solo soprano, percussion and piano ; (2012) - Whitacre, Eric 1970- (Chester Music, 2013)
Inspired by the Olympic motto "Citius, altius, fortius," this work includes text in Latin from Pindar's first Olympian ode, as well as some English words and nonsense syllables